Cognitive interest encouragement model for academic physical education: psychological and educational benefits - Sazonov, I.Y.; Tarasevich, I.V.; Bryzgalov, I.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test benefits of a new cognitive interest encouragement model for academic physical education system. Methods and structure of the study. The new cognitive interest encouragement model was developed on the following educational provisions: personality-sensitive approach in the physical education service design and management; axiological design of the physical education service; physical education service customization and individualization requirements; academic progress rating/ scoring system. We sampled for the cognitive interest encouragement model the 3-4-year students (n=80) whose progress was tested by the following pre- versus post-experimental tests: V.S. Yurkevich Cognitive Interest Intensity Questionnaire Survey; and T. Ehlers Personal Success Motivations and Failure Avoidance test. The cognitive interest encouragement model includes the following components: (1) Active and interactive teaching methods including heuristic discussions, problem-solving analyses, situational problems etc. to develop the professional competences; (2) Extracurricular activities geared to spur up cognitive interest in the future professional service. Result and conclusion. The new cognitive interest encouragement model for academic physical education system was tested beneficial as demonstrated by the sample’s progress in the physical education theory and practice including the professional knowledgebase and skills of the future physical education and sport specialists, with special benefits for the senior students’ motivations for success in their professional careers.